Usage of electronic resources by the students of engineering colleges in southern Tamilnadu, India - Chinnasamy, K.; Ravikumar, S. (Qualitative and Quantitative Methods in Libraries, 2019)
This paper is an attempt to study the usage of electronic resources among the students of engineering colleges in Southern Tamilnadu. This study requires both primary and secondary data. The primary data are collected from the respondents at engineering colleges by using questionnaire. The random sampling method was adopted for collecting primary data. A sample including engineering students were chosen from 10 selected engineering colleges in Southern Tamilnadu, India. A total number of 450 questionnaires were distributed. Secondary data are collected from various books, journals, magazines, newspapers and records. From this study, it is clear that majority of the respondents report the privacy problem is the prime problem in using electronic resources and they need workshop and classes for the effective use of e-resources.